2022
DOI: 10.1093/ajhp/zxac233
|View full text |Cite
|
Sign up to set email alerts
|

Publication rates of pharmacy residents involved in a team-based research program

Abstract: Disclaimer In an effort to expedite the publication of articles, AJHP is posting manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Hence, although clinical specialists could significantly contribute to the generation of new knowledge, they may not have the time, incentive, or proper training and resources to devote to scholarship and research activities, resulting in missed opportunities for publication. Previous studies (Miller et al, 2021;Bennett et al, 2022) have shown that graduates who took a faculty position were more likely to have subsequent publications after residency graduates than those who took a clinical specialist position. A few different strategies have been implemented to provide development of research and scholarship skills for residents, including the flippedresearch model, increased research skill development sessions, multi-site resident research projects, dedicated research time, and the establisnment of research committees (Dagam et al, 2017;Shafeeq et al, 2019;Adeosun & Haines, 2020;Frederick et al, 2020;Darko et al, 2021;Johnson et al, 2021;Morbitzer et al, 2021;Bennett et al, 2022;Olson et al, 2015;.…”
Section: Involvement In Research and Scholarship Activitiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Hence, although clinical specialists could significantly contribute to the generation of new knowledge, they may not have the time, incentive, or proper training and resources to devote to scholarship and research activities, resulting in missed opportunities for publication. Previous studies (Miller et al, 2021;Bennett et al, 2022) have shown that graduates who took a faculty position were more likely to have subsequent publications after residency graduates than those who took a clinical specialist position. A few different strategies have been implemented to provide development of research and scholarship skills for residents, including the flippedresearch model, increased research skill development sessions, multi-site resident research projects, dedicated research time, and the establisnment of research committees (Dagam et al, 2017;Shafeeq et al, 2019;Adeosun & Haines, 2020;Frederick et al, 2020;Darko et al, 2021;Johnson et al, 2021;Morbitzer et al, 2021;Bennett et al, 2022;Olson et al, 2015;.…”
Section: Involvement In Research and Scholarship Activitiesmentioning
confidence: 92%
“…However, aspects missing from these requirements include submitting the manuscript for peer review and developing other types of scholarship, such as review articles or case reports. There is variability within residency programmes regarding the requirement to submit residency projects for peer review, as evidenced by the residency publication rates ranging from 2-86% (O'Dell & Shah, 2012;Olson et al, 2012;Irwin et al, 2013;Olson et al, 2015;Cabanas, Bridgeman & Hermes-DeSantis, 2018;Morbitzer et al, 2019;Weathers, Ercek & Unni, 2019;Miller et al, 2021;Bennett et al, 2022;Swan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Research experience is also beneficial for students seeking postgraduate training, being associated with increased invitations for pharmacy residency interviews and improved residency match rates 7,17,18 . Formal research training during residency is associated with increased confidence in statistical analysis and critique of the literature, future publication rates, and potential independent researchers who can train future learners 6,19–22 . For residents pursuing academia, strong training in clinical research or scholarship of teaching and learning (SoTL) may better prepare new faculty members to successfully meet the expectations for all pillars of their role 23 …”
Section: Benefits Of Learners In Researchmentioning
confidence: 99%
“…7,17,18 Formal research training during residency is associated with increased confidence in statistical analysis and critique of the literature, future publication rates, and potential independent researchers who can train future learners. 6,[19][20][21][22] For residents pursuing academia, strong training in clinical research or scholarship of teaching and learning (SoTL) may better prepare new faculty members to successfully meet the expectations for all pillars of their role. 23 Benefits afforded to research mentors and sponsoring institutions are less rigorously studied in pharmacy literature.…”
mentioning
confidence: 99%
“…Require participation in the presentation and publication submission processes as part of the project experience because these are only fully understood once an individual has undergone the activities required Establish presentation and publication expectations among residents and mentors for the project early in the year, including expectations for what is necessary to be an author and a communication plan for post-residency follow-up. 5 A research "contract" agreement between residents and mentors to hold all accountable through project completion may be useful in this regard Encourage mentors to complete project submission when the graduated resident is unable or unwilling to do so Provide incentives for presentation and journal submissions to complement program requirements and serve as a positive alternative to mandatory submission Use team-based research, formal writing, and research development programs, projects with IRB approval, non-pharmacy coinvestigators, and results included at the time of abstract submission as methods to increase presentation and publication rates [52][53][54][55][56] Choose an appropriate journal for submission of the work…”
Section: Create a Culture And Provide Mentorship To Support The Pursu...mentioning
confidence: 99%